English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-05-31 09:59:58 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

if you ment x^2 - 10x + 7 = 0, then you can solve it like this:
x^2 - 10x + 7 = 0
a = 1
b = -10
c = 7
x = (- b +/- sqrt(b^2 - 4ac))/(2a)
x = (- (- 10) +/- sqrt((-10)^2 - 4(1)(7))/(2(1))
x = (10 +/- sqrt( 100 - 28 ) ) / 2
x = ( 10 +/- sqrt( 72 ) ) / 2
x = ( 10 +/- sqrt( 2^3 * 3^2) ) /2
x = ( 10 +/- 2 * 3 sqrt( 2 ) ) /2
x = ( 10 +/- 6 sqrt( 2 ) ) /2
x = 5 +/- 3 sqrt( 2)
x = 5 + 3 sqrt( 2 ), x = 5 - 3 sqrt( 2 )

2007-05-31 10:09:39 · answer #1 · answered by Alex 4 · 0 1

Answer is x1 = 5 + sqrt (18), x2 = 5 - sqrt (18)
<>

2007-05-31 10:04:44 · answer #2 · answered by Alas 2 · 0 1

yeah, guys right, your equation is not a quadratic

2007-05-31 10:07:32 · answer #3 · answered by Anonymous · 2 0

Your equation is not quadratic.

2007-05-31 10:03:41 · answer #4 · answered by Robert L 7 · 2 0

fedest.com, questions and answers